A novel sorption-based approach to identify water transitions in red water lily (Nymphaea × rubra) - Traiphop Phahom; Kamolwan Soubsub; Singhanat Phoungchandang (International Journal of Food Properties, 2025)
Red water lily is a promising alternative food material due to its nutritional composition and bioactive compounds. This study proposed a novel approach to identify water transition points in different parts of red water lily (peduncle, petiole, rhizome, petal and leaf) and investigate their relationships with desorption characteristics, nutritional composition, and antioxidant properties. Desorption isotherms were determined using convective air drying (50, 60 and 70°C) and microwave drying (450, 720 and 900W). Peleg model was the best described desorption behavior, exhibiting the highest coefficient of determination (R2 ≥ 0.998) and the lowest chi-square (χ2 ≤ 16.50), root mean square error (RMSE ≤ 11.00) and standard error of estimate (SEE ≤ 3.47). Water transition points varied from 0.024 to 0.505 (monolayer – multilayer) and 0.889 to 0.966 (multilayer – solvent and free water). The rhizome contained the highest carbohydrate (70% d.b.) and flavonoid content (28 mg QE/g dw), while the petal and leaf exhibited superior antioxidant properties, with the highest DPPH scavenging activity (1,270 and 1,090 μmol TE/g dw) and ferric reducing antioxidant power (1,347 and 1,017 μmol Fe (II)/g dw). Multivariate analysis revealed distinct functional and compositional differences, supporting the targeted use of red water lily parts. This approach aids in optimizing drying and storage of plant-based foods.